Feasibility and willingness to pay for dengue vaccine in the threat of dengue fever outbreaks in Vietnam - Nguyen LH; Tran BX; Do CD; Hoang CL; Nguyen TP; Dang TT; Thu Vu G; Tran TT; Latkin CA; Ho CS; Ho RCM (Patient Preference and Adherence, 2018)
Long Hoang Nguyen,1 Bach Xuan Tran,2–4 Cuong Duy Do,5 Chi Linh Hoang,6 Thao Phuong Nguyen,2 Trang Thi Dang,2 Giang Thu Vu,7 Tung Thanh Tran,7 Carl A Latkin,3 Cyrus S Ho,8 Roger CM Ho9 1Department of Public Health Sciences, Karolinska Institutet, Stockholm, Sweden; 2Institute for Preventive Medicine and Public Health, Hanoi Medical University, Hanoi, Vietnam; 3Department of Health, Behavior, and Society, Bloomberg School of Public Health, Johns Hopkins University, Baltimore, MD, USA; 4Vietnam Young Physician Association, Hanoi, Vietnam; 5Department of Infectious Diseases, Bach Mai Hospital, Hanoi, Vietnam; 6Center of Excellence in Behavioral Medicine, Nguyen Tat Thanh University, Ho Chi Minh city, Vietnam; 7Institute for Global Health Innovations, Duy Tan University, Da Nang, Vietnam; 8Department of Psychological Medicine, National University Hospital, Singapore, Singapore; 9Department of Psychological Medicine, Yong Loo Lin School of Medicine, National University of Singapore, Singapore Background: The escalation of dengue fever (DF) cases in recent years and the occurrence of a large-scale DF outbreak in 2017 underline the importance of dengue vaccines in Vietnam. Given the potential benefits of the dengue vaccines and the need for copayment by the private sector, this study aims to evaluate the willingness to pay (WTP) for the dengue vaccines in patients with DF in Northern Vietnam. Methods: A cross-sectional study was conducted on 330 in-and-out patients with DF admitted to the Bach Mai Hospital. We used the contingent valuation method to evaluate the WTP for dengue vaccines. Socioeconomic and clinical characteristics were also investigated. Multivariate interval and logistic regression models were used to estimate the average amount of WTP and identify the factors associated with the WTP. Results: Around 77.3% patients were willing to pay an average amount of US$ 67.4 (95% CI=57.4–77.4) for the vaccine. People of higher ages, those having health insurance, those traveling in the past 15 days or suffering from anxiety/depression were less likely to be willing to pay for the dengue vaccine. However, people having a longer duration of DF or having problems with mobility were positively associated with WTP for the dengue vaccine. Patients educated to more than high school levels (Coeff.=31.31; 95% CI=3.26–59.35), those in the richest quintile (Coeff.=62.76; 95% CI=25.40; 100.13), or those having a longer duration of the disease (Coeff.=6.18; 95% CI=0.72–11.63) were willing to pay a higher amount. Conclusion: This study highlights a relatively high rate and amount of WTP for the dengue vaccine among patients with DF. Psychological counseling services as well as educational campaigns should be undertaken to improve the WTP for the vaccine. Moreover, government subsidies should be given to increase the coverage of the vaccine in the future, especially for the poor. Keywords: dengue, vaccine, willingness to pay, contingent valuation, Vietnam